Contact Angle Determination in Multicomponent Lattice Boltzmann Simulations (Communications in Computational Physics, 2020)
Droplets on hydrophobic surfaces are ubiquitous in microfluidic applicationsand there exists a number of commonly used multicomponent and multiphaselattice Boltzmann schemes to study such systems. In this paper we focus on a popularimplementation of a multicomponent model as introduced by Shan and Chen. Here,interactions between different components are implemented as repulsive forces whosestrength is determined by model parameters. In this paper we present simulations ofa droplet on a hydrophobic surface. We investigate the dependence of the contact angleon the simulation parameters and quantitatively compare different approaches todetermine it. Results show that the method is capable of modelling the whole range ofcontact angles. We find that the a priori determination of the contact angle is dependingon the simulation parameters with an uncertainty of 10% to 20%.